Elementary School Students' Moral Reasoning in Resolving Moral Dilemmas: A Case Study of Pre-Conventional Stage Persistence - Agustin, Mitha Kirana; Syaodih, Ernawulan; Supriatna, Nana (Papanda Publisher, 2025)
Moral reasoning development through moral dilemmas represents a critical component of character education in elementary schools. However, declining empathy and increasing bullying incidents indicate significant gaps in students' moral reasoning capabilities. This study analyzed elementary school students' moral reasoning in resolving moral dilemmas, examining reasoning forms, developmental stages based on Kohlberg's theory, student interpretations, and influencing factors. Employing a qualitative case study approach, this research involved Grade III and V students at SD Negeri Pasirimpun, Sumedang City, Indonesia. Data were collected through semi-structured teacher interviews, moral dilemma essay assessments, and classroom observations, then analyzed thematically using triangulation and member checking to enhance trustworthiness. Findings revealed that 70% of Grade V students and 53% of Grade III students remained at the pre-conventional stage, where moral decisions were driven by punishment avoidance or reward-seeking rather than internalized principles. Only 20% of students demonstrated autonomous moral reasoning based on moral awareness. Internal factors (motivation, empathy, personal experience) and external factors (teachers, family, peer influence, social media) significantly influenced moral reasoning processes. A critical gap existed between moral knowledge and consistent moral action. These findings underscore the necessity of synergy among schools, families, and communities in building strong moral reasoning foundations through systematic interventions emphasizing dialogue, perspective-taking, and critical reflection rather than mere rule compliance.